Organic amendments of soil and its effect on the NPK contents in rice plants grown on saline soil - Hossain, MS; Khan, HR; Akter, S (Bangladesh Journal of Scientific and Industrial Research, 2018)
The potential and effectiveness of the indigenous organic amendments such as rice hull (RH), rice straw (RS) and sawdust (SD) at the rates of 0, 2 and 4 t ha-1, respectively on N, P and K contents of BRRI Dhan-47 grown on saline soil under variable moisture (field moist: FM and 2-5 cm standing water: SW) levels were evaluated in the field experiment. The N, P and K contents in the shoot at maturity stage of rice increased significantly (p<0.05) by the individual and the combined application of these amendments. The maximum contents of N (26.7 g kg-1: FM and 25.7 g kg-1: SW) were attained by the T27 (RH4SD4RS4) followed by the T26 (RH4SD4RS2) treatments. Among the three types of amendments regardless of their doses, the application of RS exerted best response (16.75 g N kg-1) followed by SD (16.35 g N kg-1) and RH (16.04 g N kg-1) in increasing N content of rice plants at field moist condition of the soil. The maximum P contents (2.49 g kg-1: FM and 2.67 g kg-1: SW) were recorded by the T27 (RH4SD4RS4) followed by the T26 (RH4SD4RS2) treatments and the lowest contents of P (0.40 g kg-1: FM and 0.42 g kg-1: SW) were obtained from the control plots. The content of P in rice shoots was slightly higher in SW than that of FM conditions. The maximum contents of K (18.2 g kg-1 in FM and 15.8 g kg-1 in SW) were obtained by the application of RH4SD4RS4 (T27) followed by the RH4SD4RS2 (T26) and the lowest contents of K (2.8 g kg-1: FM; 2.7 g kg-1: SW) were determined in the control plots. The contents of N and K in rice shoots were slightly higher in the FM than those of the SW conditions regardless of these amendments. Bangladesh J. Sci. Ind. Res.53(4), 297-304, 2018